Synergistic Effect of PbI2 Passivation and Chlorine Inclusion Yielding High Open‐Circuit Voltage Exceeding 1.15 V in Both Mesoscopic and Inverted Planar CH3NH3PbI3(Cl)‐Based Perovskite Solar Cells. (26th September 2016) - Jiang, Fangyuan; Rong, Yaoguang; Liu, Huawei; Liu, Tiefeng; Mao, Lin; Meng, Wei; Qin, Fei; Jiang, Youyu; Luo, Bangwu; Xiong, Sixing; Tong, Jinhui; Liu, Yun; et al.
Abstract : Enhancing open‐circuit voltage in CH3 NH3 PbI3 (Cl) perovskite solar cells has become a major challenge for approaching the theoretical limit of the power conversion efficiency. Here, for the first time, it is demonstrated that the synergistic effect of PbI2 passivation and chlorine incorporation via controlling the molar ratio of PbI2, PbCl2 (or MACl), and MAI in the precursor solutions, boosts the open‐circuit voltage of CH3 NH3 PbI3 (Cl) perovskite solar cells over 1.15 V in both mesoscopic and inverted planar perovskite solar cells. Such high open‐circuit voltage can be attributed to the enhanced photoluminescence emission and carrier lifetime associated with the reduced trap densities. The morphology and composition analysis using scanning electron microscopy, X‐ray diffraction measurements, and energy dispersive X‐ray spectroscopy confirm the high quality of the optimized CH3 NH3 PbI3 (Cl) perovskite film. On this basis, record‐high efficiencies of 16.6% for nonmetal‐electrode all‐solution‐processed perovskite solar cells and 18.4% for inverted planar perovskite solar cells are achieved. Abstract : A synergistic effect of PbI2 passivation and chlorine incorporation induces suppression of non‐radiative recombination in a perovskite film. This leads to a high open‐circuit voltage exceeding 1.15 V in both mesoscopic and inverted planar CH3 NH3 PbI3 (Cl)‐based perovskite solar cells.